Considering the effects of temperature × nutrient interactions on the thermal response curve of carrying capacity. Issue 4 (8th March 2019) - Lemoine, Nathan P.
Abstract: Climate warming will likely destabilize populations or drive consumers locally extinct. These predictions arise from consumer–resource models incorporating temperature‐dependent parameters, and the accuracy of these predictions hinges on the validity of temperature scalings for each parameter. Among all parameters, carrying capacity ( K ) is the most ill‐defined and the temperature scaling of this parameter has no empirically verified foundation. Most studies assume that K declines exponentially with warming, but others have assumed a positive or no relationship between K and temperature. Here, I developed a theoretical foundation for a temperature scaling of K based on physiological principles of temperature and nutrient limitation of phytoplankton growth. The trade‐off between thermodynamics and nutrient uptake yields a unimodal thermal response curve for K, and this prediction is supported by empirical data on both phytoplankton and insects. Analyses of consumer–resource models demonstrate the primacy of K in determining predictions of coexistence and stability. Since K exerts a dominant influence on model predictions, ecologists should carefully consider the temperature scaling of K for the species and region in question to ensure accurate estimates of population stability and extinction risk.